2022
DOI: 10.4102/sajr.v26i1.2294
|View full text |Cite
|
Sign up to set email alerts
|

An audit of CT brain findings in adults with new-onset seizures in a resource restricted setting in South Africa

Abstract: Background Globally, adults presenting with seizures account for 1% – 2% of visits to emergency departments (EDs), of which 25% are new-onset seizures. Neuroimaging is essential as part of the initial workup. Multiple studies have demonstrated abnormal CT brain (CTB) findings in these patients. Objectives To review the CTB findings in adults presenting with new-onset seizures in a resource restricted setting. Method A retrospective review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A total of 9 potential predictors were preselected based on previously reported literature, expert consensus, simplicity, and their availability in general ED [ 5 , 11 13 , 16 ]. Demographic data: age, gender, clinical data: Glasgow coma scale (GCS) of 8≤, 9–13, >13, new-onset focal neurological deficit (absence or presence) defined as: a set of symptoms or sign in which causation can be localized to an anatomic site in the central nervous system [ 17 ], previous CT head scans status (absence, normal or abnormal), history of malignancy (absence or presence), history of cerebrovascular accident (CVA) (absence or presence), Epilepsy (absence or presence) defined as: two unprovoked seizures occurring more than 24 h apart; a single unprovoked seizure if recurrence risk is high (ie, >60% over the next 10 years); or a diagnosis of an epilepsy syndrome [ 18 ], AWS (present or absence) defined as the present of autonomic hyperactivity (sweating, tachycardia); increased hand tremor; insomnia; nausea or vomiting; transient visual, tactile, auditory hallucinations or illusions; psychomotor agitation; anxiety; or tonic-clonic seizures caused by abruptly discontinued of previous large consumed alcohol [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 9 potential predictors were preselected based on previously reported literature, expert consensus, simplicity, and their availability in general ED [ 5 , 11 13 , 16 ]. Demographic data: age, gender, clinical data: Glasgow coma scale (GCS) of 8≤, 9–13, >13, new-onset focal neurological deficit (absence or presence) defined as: a set of symptoms or sign in which causation can be localized to an anatomic site in the central nervous system [ 17 ], previous CT head scans status (absence, normal or abnormal), history of malignancy (absence or presence), history of cerebrovascular accident (CVA) (absence or presence), Epilepsy (absence or presence) defined as: two unprovoked seizures occurring more than 24 h apart; a single unprovoked seizure if recurrence risk is high (ie, >60% over the next 10 years); or a diagnosis of an epilepsy syndrome [ 18 ], AWS (present or absence) defined as the present of autonomic hyperactivity (sweating, tachycardia); increased hand tremor; insomnia; nausea or vomiting; transient visual, tactile, auditory hallucinations or illusions; psychomotor agitation; anxiety; or tonic-clonic seizures caused by abruptly discontinued of previous large consumed alcohol [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to surveys [ 10 ], decision support tools show promise in helping emergency physicians effectively utilize CT head scans. Many studies have demonstrated the potential factors that associated with positive finding on CT head scans such as Age, focal neurological deficit, history of malignancy, alcohol withdrawal symptoms (AWS) [ 5 , 11 13 ]. However, studies focusing on the utilization of these factors to develop clinical prediction tools for supporting the use of CT head scans in patients with seizures in resource-constrained settings are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted by Das and Barman (2018), as well as Mabaso (2020) on ways to introduce an HRIS that has fully assimilated HR mechanisms that can be used in the effectiveness of organisations' performance, are essential. This perhaps could deprive some organisations not able to make use of ISs such as HRIS to ascertain workers that are due for incentives for their additional effort be rewarded accordingly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For some time now, the public healthcare sector in developing nations has yet to live up to its promises of good healthcare services. For example, Lema (2018) and Mabaso (2020) decried the state of public hospitals in South Africa (SA) and Ethiopia. Equally, Grobler, Wärnich and Mokobane (2018) and Matimbwa and Masue (2019) mentioned the lack of qualified personnel to manage public healthcare facilities.…”
Section: Introductionmentioning
confidence: 99%